Scaling the Next Generation of Seasonal Climate Forecasting tools through the West African Regional Climate Outlook Forum - Segnon, Alcade C; Mohamed, Hamatan; Minoungou, Bernard; Gadédjisso-Tossou, Agossou; Halidou, Tinni Seydou; Ali, Abdou; Obossou, Esdras; Zougmoré, Robert B. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Ninety participants, including 15 women, from the 17 National Meteorological and Hydrological Services (NMHSs) in West and Central Africa were successfully trained on the NextGen/PyCPT tool through AICCRA side during 2022 PRESASS. NMHS staff have gained a good understanding of the benefits of the NextGen/PyCPT tool as a vital element in the development of better seasonal forecasts at national and regional levels, and how to use PyCPT. About half of the trainees planned to share the knowledge, skills and resources acquired during the training with their colleagues at institutional level. Follow up training was organized to selected AICCRA anchored and non-AICCRA countries in West Africa to strengthen the pool of expertise in the use of the NextGen tools. This needs to be strengthened in the future.